Evaluation of Hevea brasiliensis (latex timber clone: RRIM 2001 and RRIM 3001) in relation to different water stress - Mokhatar, Shafar Jefri; Wan Daud, Wan Mohamed Noordin; Md Zamri, Nursyazwina (Science Publications, 2011)
Problem statement: Rubber, Hevea brasiliensis, has been traditionally planted in the humid tropics, which is characterized by high rainfall throughout the year. However, due to an increase in world's demand for rubber, future planting will be established in dry areas, characterized by prevalence water stress. Utilizing limited resource, in dry areas or to use water wisely is very important. This study provides a detail evaluation of morphological and physiological responses of rubber trees at nursery stage in relation to different water stress. Approach: Two new latex timber clones from Malaysia Rubber Board (MRB), RRIM 2001 and RRIM 3001 were used in this study. Five levels of treatment were used; plants irrigated for every two days, five days, 10 days, 15days and everyday which acted as control. The experimental design used was a Completely Randomized Block Design (RCBD) with four replications. Results: Fundamental changes of plant growth and physiological responses showed that treatment with well watered for clone RRIM 2001 (T1) had higher values than other treatments. Harvest index highest in well watered (T1) with mean 20.73, while T5 were lowest with the mean 5.03. Stomata conductance showed significant difference between T6 with 0.161 µmol m-2s-1 compared to under stress treatments with 0.00 mol m-2s-1. There was treatment failure to adapt to water stress at treatments withholding water for 15days followed by treatments 10days and five days. Conclusion: RRIM 2001 and RRIM 3001 clones had responded to water stress by indicating changes in morphological and physiological responses. This indicated that Hevea brasiliensis cannot withstand water stress.